How do citizens envision democratic participation for sustainable futures? A reflection on co-created innovations - Inês Campos; Doris Fuchs; Petteri Repo; Vanessa Buth; Kiat Ng; João Limão; Erica Löfström; David Lamas; Christian Klöckner (Ecological Economics, 2026)

What roles can democracy labs play in co-creating democratic innovations for sustainability? - Inês Campos; Doris Fuchs; Petteri Repo; Wander Jager; Christian Klöckner; Shaoni Wang; David Lamas; Francesc Cots; Eugenio Barchiesi; Erica Löfström; Daniel Peniche; Yulia Sion; et al. (Socio-Ecological Practice Research, 2024)
This perspective essay proposes Democracy Labs as new processes for developing democratic innovations that help tackle complex socio-ecological challenges within an increasingly unequal and polarised society, against the backdrop of democratic backsliding. Next to the current socio-ecological crisis, rapid technological innovations present both opportunities and challenges for democracy and call for democratic innovations. These innovations (e.g., mini-publics, collaborative governance and e-participation) offer alternative mechanisms for democratic participation and new forms of active citizenship, as well as new feedback mechanisms between citizens and traditional institutions of representative democracy. This essay thus introduces Democracy Labs, as citizen-centred processes for co-creating democratic innovations to inspire future transdisciplinary research and practice for a more inclusive and sustainable democracy. The approach is illustrated with examples from a Democracy Lab in Lisbon, reflecting on requirements for recruiting participants, the relevance of combining sensitising, reflection and ideation stages, and the importance of careful communication and facilitation processes guiding participants through co-creation activities.